2015
DOI: 10.7314/apjcp.2015.16.9.3617
|View full text |Cite
|
Sign up to set email alerts
|

Update knowledge on cervical cancer incidence and prevalence in Asia

Abstract: Cervical cancer is the second most common cause of cancer-related death among women worldwide, with over 500,000 new cases diagnosed annually and 50% mortality rate in Asia. In the United States, approximately 10,370 new cases of cervical cancer are diagnosed annually, and estimated 3,710 deaths occur from the disease, making it the sixth most common cause of malignancy among American women. This study aims to provide awareness about cervical cancer as well as an updated knowledge about the prevalence and inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…Human papillomavirus (HPV) infection is found to be an essential causative factor in almost all cases of cervical carcinomas throughout the world, with 70% of the cases attributable to HPV oncogenic subtypes 16 and 18 [5]. It is quite alarming that more than one-third of all patients diagnosed with cervical carcinoma ultimately die when it is preventable and curable at an early stage, and around 50-90% of females who develop or die due to cervical cancer have never been screened [3,[8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Human papillomavirus (HPV) infection is found to be an essential causative factor in almost all cases of cervical carcinomas throughout the world, with 70% of the cases attributable to HPV oncogenic subtypes 16 and 18 [5]. It is quite alarming that more than one-third of all patients diagnosed with cervical carcinoma ultimately die when it is preventable and curable at an early stage, and around 50-90% of females who develop or die due to cervical cancer have never been screened [3,[8][9].…”
Section: Introductionmentioning
confidence: 99%
“…13 It is the second most common cause of cancerrelated death among women worldwide and 50% mortality rate is seen in Asia while in Nepal 1,367 women die from the disease every year. 12,13 Late stage at diagnosis is one of the causes for their lowered survival rates. The lack of awareness regarding HPV infection, screening and availability of vaccine for its prevention in the general populations and health professionals in a large scale as well as other cultural and social issues has led to the presentation of cervical cancer in the advanced stages in the developing countries like ours.…”
Section: Cervical Cancermentioning
confidence: 99%
“…The lack of awareness regarding HPV infection, screening and availability of vaccine for its prevention in the general populations and health professionals in a large scale as well as other cultural and social issues has led to the presentation of cervical cancer in the advanced stages in the developing countries like ours. 13,[15][16][17] Besides the mortality, invasive cervical cancers have a huge impact in sexual life (dyspareunia and reduced autonomic response), reproductive and bladder function (voiding SUREOHPV 6LJQL¿FDQW PRUELGLWLHV UHVXOWLQJ IURP WKH chronic pain (due to bony invasions), renal failure GXH WR XUHWHULF LQYROYHPHQW ¿VWXOD DQG GLVFKDUJH are also common. Like in other studies done in Nepal, in this study also maximum women with carcinoma cervix were found to be in their 5 th and 6 th decade.…”
Section: Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common cancers among women around the world is cervical cancer (1). Nearly 80% of cervical cancer cases occur in developing countries (2). Cervical cancer is the second most common cause of cancer-related death among women worldwide, with over 500,000 new cases diagnosed annually and about 50% mortality rate in Asia (3).…”
Section: Introductionmentioning
confidence: 99%